RADON, THORON AND THEIR PROGENY DISTRIBUTION AND ESTIMATION OF ANNUAL EFFECTIVE DOSE AND EXCESS LIFETIME CANCER RISK IN PANATHADY, KASARAGOD DISTRICT, KERALA. Issue 1 (7th November 2019) - Mahamood, K Nadira; Prakash, V
Abstract: Radon and thoron are natural radioactive gases that tend to accumulate in the indoor environment and one of their major health implications is the ability to cause lung cancer. Present study comprises the quantification of radon and thoron activity concentrations and measurement of gamma exposure rates in different types of dwellings from the endosulfan-affected area, Panathady, Kasaragod district, Kerala. It is observed that, residents of this area were more prone to various diseases and health problems including cancer. The LR-115 type II solid state nuclear track detectors with single entry pin-hole based dosemeters have been used for the measurement of 222 Radon and 220 Rn activity concentrations. The assessment of radiological parameters such as annual effective doses and excess lifetime cancer risk has also been done in order to understand the dose level and the associated risk. The estimated values have been compared with the limit recommended by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) and International Commission on Radiological Protection (ICRP). The average indoor radon and thoron activity concentrations observed in these dwellings were 134 ± 30 and 111 ± 28 Bq m −3, respectively. The estimated activity concentrations, effective doses, etc. are found to be within the recommended level by the UNSCEAR or ICRP.